2009
DOI: 10.1007/s11604-008-0293-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging findings of extrapelvic endometriosis of the round ligament

Abstract: A 31-year-old woman presented with a mass in her groin accompanied by intense pain during the menstrual period. A poorly circumscribed, elastic, hard mass was palpable in her right inguinal region. Magnetic resonance imaging showed that the mass had continuity with the inguinal course of the round ligament of the uterus. The mass lesion was well enhanced with high intensity on diffusion-weighted imaging. An operation was performed, and the histological diagnosis was endometriosis of the round ligament. After o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Theories reported earlier are haematogenic or lymphogenic dissemination of endometriosis cells from the abdominal cavity and metaplasia [ 11 ]. Moreover, spontaneous endometriosis located in the inguinal region is thought to develop from direct extension from pre-existing endometriosis along the round ligament [ 28 ]. This mechanism may also have played a role in our two patients with spontaneous AWE lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Theories reported earlier are haematogenic or lymphogenic dissemination of endometriosis cells from the abdominal cavity and metaplasia [ 11 ]. Moreover, spontaneous endometriosis located in the inguinal region is thought to develop from direct extension from pre-existing endometriosis along the round ligament [ 28 ]. This mechanism may also have played a role in our two patients with spontaneous AWE lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies use the value of 9 mm for uterosacral ligament thickness to define involvement. Bazot et al and Jarlot et al used rather irregularity and asymmetry of uterosacral ligaments to define their involvement because they observed that ligaments measuring less than 9 mm may be involved (Figure 4) [5, 11, 13, 35]. Posterior cul-de-sac lesions include retroperitoneal lesions and intraperitoneal infiltrating lesions, which are divided into rectovaginal septum lesions (type I), posterior wall forniceal lesions (type II), and hourglass shaped lesions (type III).…”
Section: Mri Techniquementioning
confidence: 99%
“…CA 125 level was normal in our case. US and CT are not diagnostic; however, US features of mixed echogenicity and lack of blood flow can be suggestive while CT helps define anatomy and proximity to vessels 4. Treatment options include expectant management, hormonal therapy or complete surgical excision with avoidance of spillage to prevent recurrence 3.…”
Section: Discussionmentioning
confidence: 99%